Comparison of Pyroxasulfone to Soil Residual Herbicides for Glyphosate Resistant Palmer Amaranth Control in Glyphosate Resistant Soybean. Issue 1 (1st December 2013) - Grey, Timothy L.; Cutts, George S.; Newsome, Larry J.; Newell, Sanford H.
Abstract : Glyphosate‐ and acetolactate synthase (ALS)‐resistant Palmer amaranth ( Amaranthus palmeri S. Wats.) has become the most common and troublesome weed in multiple crops in the southeast United States. Pyroxasulfone inhibits biosynthesis of very long chain fatty acids (VLCFAs) and can provide soil residual weed control. However, there has been little information about pyroxasulfone for control of weeds in the southeastern United States. Experiments were conducted in 2010 and 2011 in fields infested with multiple weeds including glyphosate‐ and ALS‐resistant Palmer amaranth to compare herbicides with different modes of action. These included pyroxasulfone, a VLCFA inhibitor, S ‐metolachlor (a VLCFA inhibitor), flumioxazin, a protoporphyinogen oxidase (PROTOX) inhibitor, metribuzin, a photosystem II inhibitor, fomesafen (a PROTOX inhibitor), and glyphosate, an enolpyruvylshikimate 3‐phosate synthase inhibitor. Soybean [ Glycine max (L.) Merr.] (Asgrow DP7870 RR in 2010 and Asgrow AG6931 in 2011) were conventionally planted and evaluated for injury, stand density, and yields. Weed control was based on evaluation of glyphosate‐ and ALS‐resistant Palmer amaranth, sicklepod [ Senna obtusifolia (L.) H.S.Irwin & Barneby], Florida beggarweed [ Desmodium tortuosum (Sw.) DC.], smallflower morningglory [ Jacquemontia tamnifolia (L.) Griseb.], and wild poinsettia ( Euphorbia heterophylla L.). There were no effects on soybean emergence for any preemergence (PRE) herbicide treatment. There was no significant soybean injury with pyroxasulfone at rates of 0.86 to 2.57 oz a.i./acre for PRE or early postemergence (EPOST) application. For season‐long residual control of glyphosate‐ and ALS‐resistant Palmer amaranth, pyroxasulfone at 1.28 oz a.i./acre and greater were required for 87% and greater control. Pyroxasulfone plus flumioxazin at 1.50 and 1.01 oz a.i./acre PRE, respectively, provided season‐long Palmer amaranth control at 99%. Pyroxasulfone also controlled Florida beggarweed and smallflower morningglory. A combination of PRE, EPOST, and postemergence (POST) herbicide applications (glyphosate or fomesafen) were required for sicklepod and wild poinsettia control. Maximum yields required the combination of residual PRE and contact and residual EPOST herbicide applications. Successful soybean production in the southeast United States will require crop rotation and use of multiple herbicide modes of action PRE, EPOST, and POST to minimize herbicide resistant Palmer amaranth related issues.